The Seed Populations in the Earth's Outer Radiation Belt During the Main Phase of Magnetic Storms: A Statistical Study. Issue 3 (7th March 2022) - Wang, Xu; Tang, Chaoling; Ni, Binbin; Su, Zhengpeng; Zhang, Jichun
Abstract: Using the data from Van Allen Probes, we investigate in detail the seed populations in the outer radiation belt during the storm main phase. Based on the different flux variations of the seed electrons before the storm and around the storm peak, these storm events are divided into "flux decay events, " "flux enhancement events" and "strong flux enhancement events." For flux decay events, a shorter storm main phase (≤12 hr) and smaller southward interplanetary magnetic field (IMF) and solar wind electric field (−15 nT < B z min < −5 nT, 2 mV/m < E y max < 7 mV/m) are found. For flux enhancement events, large southward B z min and E ymax (−29 nT < B z min < −10 nT, 5 mV/m < E y max < 11 mV/m) for the shorter main phase or smaller southward B z min and E y max (−23 nT < B z min < −5 nT, 3 mV/m < E y max < 11 mV/m) for the longer main phase (>12 hr) are observed. For strong flux enhancement events, larger southward B z min and E y max (−32 nT < B z min < −13 nT, 5 mV/m < E y max < 22 mV/m) for the shorter main phase or smaller southward B z min and E y max (−26 nT < B z min < −9 nT, 3 mV/m < E y max < 16 mV/m) for the longer main phase are observed. These suggest that the flux variations of the seed electrons during the storm main phase are highly influenced by the duration of the storm main phase, southward IMF, and solar wind electric field. Key Points: For flux decay events, the duration of the storm main phase is shorter, southward B z min and E y max are smaller For flux enhancement events, southward B z min and E y max for the events with shorter main phase are larger than those with longer main phase For strong flux enhancement events, southward B z min and E y max are larger than others under the same duration of the storm main phase